POTENSI PLTMH DI BENDUNGAN SIDAN, DESA BELOK SIDAN, KABUPATEN BADUNG - Natih Evan Bayu, I D G; Sukerayasa, I W; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p15, 2024)
The potential of new renewable energy is highly needed to support Clean Energy Bali, and one of the viable energy sources is Micro Hydro Power Plant (PLTMH). The design of the Sidan Dam PLTMH is based on the construction of the Sidan Dam area in Belok Sidan Village, Badung Regency. The planning of the Sidan Dam PLTMH only extends to the construction of the penstock. In this Capstone Project, the design of the Sidan Dam PLTMH utilizes water discharge and head height data from the Sidan Dam planning. This data is used to determine the design, type of water turbine, dimensions of the water turbine, and to determine the appropriate generator capacity. The calculation results indicate that the Sidan Dam PLTMH has a potential capacity of 290.83 kW with a Francis turbine type and a generator capacity of 472.59 Kva. It is estimated to generate an annual energy output of 1,783,396 kWh with a capacity factor 70%.